Perfil de idosos longevos frequentadores de um ambulatório de geriatria do Distrito Federal: um estudo sobre sarcopenia e sua associação com fatores de saúde e biomarcadores inflamatórios - Santos, Aline Afonso (2019)
Older elderly, individuals with 80 years of age or more, are among the population subgroup that grows in the world. Studying these individuals is part of the world agenda considering that they are the ones who face the most functional limitations and death. Sarcopenia is a progressive skeletal muscular disfunction associated to aging and is directly linked to undesirable outcomes. Many mechanisms are associated to the origin of sarcopenia and inflammation is one of the factors involved. The unbalance between pro-inflammatory and anti-inflammatory biomarkers contributes to the celular catabolic process in elderly patients. The goal of this study was to evaluate the profile of the older elderly, analyze the prevalence of sarcopenia and its association with health factors and inflammatory biomarkers. It is a cross-sectional study, in three steps. On the first step, social demographic evaluations were made and health data was collected. On the second step, inflammatory biomarkers were evaluated. Finally, on the third step, anthropometric measures along with body composition measures were taken from the patients. The sample was composed by 117 elderly with 80 years of age or more. The sarcopenia was defined through three variables: muscular strength, muscle mass and physical performance. The muscle strength was evaluated through a hand grip strength test, with a manual dynamometer, and the cases corresponding to the inferior quintile adjusted by gender and body mass index were taken into consideration. The muscle mass was identified through absorptiometry of double energy X-rays and to classify this variable two distinct approaches were selected, one where the cut-off value was 7,26 and 5,45 kg/m2 for men and women, respectively, and another where the muscle mass was adjusted by gender for the sample, taking into consideration the cases of individuals from the inferior quintile. The physical performance was evaluated through the speed of walking to go through 4,6 meters, considering the inferior quintile cases adjusted by gender and height. The individuals with low muscle strength, were categorized as possible sarcopenia. Individuals with low muscle strength and mass, were categorized as sarcopenia and, lastly, those with reduction in all three evaluated variables were categorized as severe sarcopenia. The description analysis were made through the mean, standard deviation and frequency, A Mann-Whitney non-parametric test was applied. The categorical variables were analyzed by the chi-square or Fisher’s Exact, the significance level of the analysis was 5% (p<0,05). The mean age of the participants was 83,8 years of age, 65,8% of which were women and 34,2% were men, 47% of the sample were widows and 29,1% live on their own, 44% receives three or more minimum salaries and 41,9% evaluate their own health as good or very good. Among the patients, 37,6% consider themselves to be independent to do their daily activities and 64,1% did not fall during the last year. The prevalence of sarcopenia was 4,2% and 8,5% through the Baumgartner cut-off value for muscle mass and adjusted to the sample, respectively. Cognitive impairment, functional dependency and IL-6 (p<0,05) were associated to sarcopenia. The prevalence of sarcopenia waslower than the one observed in previousstudies and was associated to health determinants and inflammatory biomarkers present in the sample. More analysis are necessary in order to evaluate different elderly profiles.